Revitalisasi Pengelolaan Jurnal IJID - Maria Ulfah Siregar; Sumarsono Sumarsono (UIN Sunan Kalijaga Yogyakarta, 2019)
IJID journal is one of scientific journal that belongs to Department of Informatics, Master and Undergraduate Programs, Faculty of Science and Technology, UIN Sunan Kalijaga. In this paper, we discuss problems that this journal faces. We describe also activities that we have done to solve those problems. Problems, such as discontinuity in publishing papers, not yet registered with DOAJ, not yet obtained national accreditation (namely Sinta), and not yet internationally recognized by Scopus index, are usual journal management problems that happened on journals. IJID editorial has conducted several treatments to combat those problems. As a result, some editions can be published. Now, IJID steps more further to apply for DOAJ and national accreditation.